Intrapartum Management of Chorioamnionitis. Issue 1 (January 2018) - Wisner, Kirsten
Abstract : The American College of Obstetricians and Gynecologists issued a new committee opinion on intrapartum management of intraamniotic infection. Our maternity nursing expert, Kirsten Wisner, covers details of the recommendations for clinical practice.